Health care utilization among patients with oesophageal and gastric cancer: the impact of initial treatment strategy and assignment of a contact nurse - Karin Dalhammar; Marlene Malmström; Magnus Sandberg; Dan Falkenback; Jimmie Kristensson (BMC, 2021)
Abstract Background Patients diagnosed with oesophageal and gastric cancer face a poor prognosis and numerous challenges of symptom management, lifestyle adjustments and complex treatment regimens. The multifaceted care needs and rapid disease progression reinforce the need for proactive and coherent health care. According to the national cancer strategy, providing coherent health care and palliative support is an area of priority. More knowledge is needed about health care utilization and the characteristics of the health care service in order to understand the readiness, accessibility and quality of current health care. The aim of this study was to describe individuals' health care use from the time of treatment decision until death, and investigate the impact of the initial treatment strategy and assignment of a contact nurse (CN) on health care use among patients with oesophageal and gastric cancer. Methods This population-based cohort study included patients who died from oesophageal and gastric cancer in Sweden during 2014-2016. Through linking data from the National Register for Oesophageal and Gastric Cancer, the National Cause of Death Register, and the National Patient Register, 2614 individuals were identified. Associations between the initial treatment strategy and CN assignment, and health care use were investigated. Adjusted incidence rate ratios (IRRs) with 95% confidence intervals (CIs) were calculated using Poisson regression. Results Patients receiving palliative treatment and those receiving no tumour-directed treatment had a higher IRR for unplanned hospital stays and unplanned outpatient care visits compared with patients who received curative treatment. Patients receiving no tumour-directed treatment also had a lower IRR for planned hospital stays and planned outpatient care visits compared with patients given curative treatment. Compared with this latter group, patients with palliative treatment had a higher IRR for planned outpatient care visits. Patients assigned a CN had a higher IRR for unplanned hospital stays, unplanned outpatient care visits and planned outpatient care visits, compared with patients not assigned a CN. Conclusions A palliative treatment strategy and no tumour-directed treatment were associated with higher rates of unplanned health care compared with a curative treatment strategy, suggesting that a proactive approach is imperative to ensure quality palliative care.